RELATIONSHIP OF MOTIVATION FOR HEALTH WITH SOME RISK FACTORS FOR DEVELOPING CARDIOVASCULAR DISEASES IN COAL INDUSTRY WORKERS WITH OCCUPATIONAL PATHOLOGY - Данилов, Игорь Петрович; Влах, Надежда Ивановна; Пестерева, Дина Викторовна; Панева, Наталия Яковлевна; Логунова, Татьяна Дмитриевна (Medicine in Kuzbass, 2022)
The subject was the relationship between the motivation for health and risk factors for developing cardiovascular diseases.The objective was the determination of the relationship between the level of motivation for health and a healthy lifestyle using the questionnaires «Index of Motivation for Health and a Healthy Lifestyle» and «Your Lifestyle» and risk factors for the development of cardiovascular diseases to assess the possibility of using questionnaires during periodic medical examinations.Study methods. A survey of 199 coal industry workers with occupational diseases was conducted. The determination of the level of motivation for health was carried out according to the questionnaires «Index of Motivation for Health and a Healthy Lifestyle» and «Your Lifestyle». Risk factors for cardiovascular disease were identified using the original questionnaire.Main results. The frequency of risk factors for cardiovascular diseases was determined, smoking was revealed in 29.1 % of respondents, arterial hypertension – in 19.5 %, diabetes mellitus – in 3.1%, body mass index over 25 – in 72.5 %, low physical activity – in 61.9 %, the presence of stressful situations – in 24.4 %, poor stress tolerance – in 34.9 % of respondents. Low motivation for health was related to a higher incidence of arterial hypertension and low physical activity, a «deviant» lifestyle was associated with a higher frequency of smoking and low physical activity.Scope of their application: Occupational pathology, occupational medicine, preventive medicine, cardiology, medical psychology.Conclusions. The relationship between the frequency of risk factors for cardiovascular diseases and the results of studies using the questionnaires «Index of Motivation for Health and a Healthy Lifestyle» and «Your Lifestyle» was revealed. The use of these questionnaires in the context of periodic medical examinations will allow identifying workers with a higher risk of cardiovascular diseases.
Keywords: occupational diseases; the coal industry; risk factors of cardiovascular diseases; motivation for health and a healthy lifestyle